Putative molecular markers of Plasmodium falciparum resistance to antimalarial drugs in malaria parasites from Ghana - Matrevi, Sena Adzoa; Adams, Tryphena; Tandoh, Kwesi Zandoh; Opoku-Agyeman, Philip; Bruku, Selassie; Ennuson, Nana Aba; Apau-Danso, Paa Kwesi; Fiagbedzi, Emmanuel; Avornyo, Mary; Myers, Charles James; Futagbi, Joy; Hagan, Oheneba Charles; et al. (Frontiers in Epidemiology, 2024)
Introduction Antimalarial drugs including artemisinin-based combination therapy (ACT) regimens and sulphadoxine-pyrimethamine (SP) are used in Ghana for malaria therapeutics and prophylaxis respectively. The genetic basis of Plasmodium falciparum development of drug resistance involves single nucleotide polymorphisms in genes encoding proteins for multiple cellular and metabolic processes. The prevalence of single nucleotide polymorphisms in nine P. falciparum genes linked to ACT and SP resistance in the malaria parasite population was determined. Methods Archived filter paper blood blot samples from patients aged 9 years and below with uncomplicated malaria reporting at 10 sentinel sites located in three ecological zones for the Malaria Therapeutic Efficacy Studies were used. The samples used were collected from 2007-2018 malaria transmission seasons and mutations in the genes were detected using PCR and Sanger sequencing. Results In all 1,142 samples were used for the study. For falcipain-2 gene (pffp2), Sanger sequencing was successful for 872 samples and were further analysed. The prevalence of the mutants was 45% (392/872) with pffp2 markers V51I and S59F occurring in 15.0% (128/872) and 3.0% (26/872) of the samples respectively. Prevalence of other P. falciparum gene mutations: coronin (pfcoronin) was 44.8% (37/90); cysteine desulfurase (pfnfs) was 73.9% (68/92); apicoplast ribosomal protein S10 (pfarps10) was 36.8% (35/95); ferredoxin (pffd) was 8.8% (8/91); multidrug resistance protein-1 (pfmrp1) was 95.2.0% (80/84); multidrug resistance protein-2 (pfmrp2) was 91.4% (32/35); dihydrofolate reductase (pfdhfr) was 99.0% (84/85); dihydropteroate synthase (pfdhps) was 72% (68/95). Discussion The observation of numerous mutations in these genes of interest in the Ghanaian isolates, some of which have been implicated in delayed parasite clearance is of great interest. The presence of these genotypes may account for the decline in the efficacies of ACT regimens being used to treat uncomplicated malaria in the country. The need for continuous monitoring of these genetic markers to give first-hand information on parasite susceptibility to antimalarial drugs to inform policy makers and stakeholders in malaria elimination in the country is further discussed.